An integrated web application for efficient restaurant management - Lim, Jarod Jia-Wei (2025)
Obesity is a condition characterized by an excess accumulation of body fat which is a major health problem prevalent in millions of people across the world and there is a consistent rise in prevalence in both adults as well as youths. In this project we propose the creation of a Personalized Nutrition and Obesity Intervention System which is investigated by providing the user with personalized diet options based on personal profiles in Mobile Application. This app is made with a primary focus on personalized nutrition, in contrast to many other apps that consider nutrition as a secondary feature. Some of its features include a menu that can be adjusted depending on the end user, features that allow users to monitor their health and features that help to promote engagement and continued use of the application. With the help of an integrated smart nutrition calculator in the mobile application, users may input personal information like age, weight, gender, activity level, and health goals to receive personalized recommendations for calorie intake. The dietary planner ensures that consumers may modify their meal plans as their health needs change by providing flexible customization based on dietary choices, allergies, and real-time feedback. There is also a diet and health option on the software where the user can record the food they take and other health aspects such as weight and Body mass index (BMI). Charts and graphs are used to show users daily activity and goals progress. Like in most mobile applications, motivational features such as daily check-ins, challenges, and point-based reward systems present in the app to enhance the users’ experience. The basic features of such applications are returning points to the activity in hope of receiving vouchers or discounts to enhance retention. In addition, multilingual support ensures that the users with different languages and culture can easily access the application thus allowing it to be used by a global population of users. Java was the main programming language used in Android Studio. To ensure its reliability and scalability other tools such as Git version control and XAMPP control panel were used for backend services. The project addresses several of the fundamental limitations of current mobile health solutions, such as the difficulty of sustaining long-term good eating habits and the lack of customization in obesity intervention tools. Through the aid of the app, the target is to fill a gap in the market by offering specialized nutrition which will empower and encourage user to achieve their desired wellness and health in nutrients.